Odpowiedzi

Najlepsza Odpowiedź!
2010-04-07T21:42:11+02:00
Z.63
2z-9= 7+x ( z czy x?? stawiam na x :-)
2x-9= 7+x
2x-x = 7+9
x = 16

2(1-x)=-3x-61+4x
2-2x = -3x-61+4x
-2x-4x+3x = -61-2
-3x = -63 |:(-3)
x = 21

2x-5(0,2x-5)=3(x-5)-20
2x-x+25 = 3x-15-20
x-3x = -35-25
-2x = -60 |:(-2)
x = 30

2x+3(22-x)=x-3(8-x)
2x+66-3x = x-24+3x
2x-3x-x-3x = -24-66
-5x = -90 |:(-5)
x = 18

2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x = 3x-42-7x-5
2x-9x-3x+7x = -42-5+5
-3x = -42 |:(-3)
x = 14

z.62
2/3x+3 1/2 = 4,3
2/3x = 4,3-3,5
2/3x = 0,8
x = 1,2

7/3+10/9x = 22/9
10/9x = 22/9 -7/3
10/9x = 1/9
x = 0,1

28/5 = 4,6+0,5x
-0,5x = -28/5+4,6
-0,5x = -1 |:(-0,5)
x = 2

10x-3,75 = 61/4
10x = 61/4+3,75
10x = 19
x = 1,9

5x-4,6 = 0,9
5x = 0,9+4,6
5x = 5,5
x = 11/10
x = 1,1

0 = 3x-0,9
-3x = -0,9
x = 0,3

3/8 = 5/2x-0,125
-5/2x = -0,125-3/8
-5/2 x =- 500/1000
-5/2 x = -0,5
x = 0,2

x/3-1/4 = 0,45 |*12
4x-3 = 5,4
4x = 5,4+3
4x = 8,4
x = 2,1

2,78-x = 1,78
-x = 1,78-2,78
-x = -1
x = 1
1 5 1